2010
DOI: 10.1128/mcb.00142-10
|View full text |Cite
|
Sign up to set email alerts
|

Genes of the Ecdysone Biosynthesis Pathway Are Regulated by the dATAC Histone Acetyltransferase Complex in Drosophila

Abstract: Uncovering mechanisms that regulate ecdysone production is an important step toward understanding the regulation of insect metamorphosis and processes in steroid-related pathologies. We report here the transcriptome analysis of Drosophila melanogaster dAda2a and dAda3 mutants, in which subunits of the ATAC acetyltransferase complex are affected. In agreement with the fact that these mutations lead to lethality at the start of metamorphosis, both the ecdysone levels and the ecdysone receptor binding to polytene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…[16][17][18] Recently, it has been reported that dTAF10 and dTAF10b have synergistic roles in the regulation of Drosophila morphogenesis and they are required for the activation of Halloween genes involved in ecdysone biosynthesis. [18][19][20] Taken together, these observations support the idea that functionally different TAFcontaining complexes participate in gene regulation.…”
Section: Introductionsupporting
confidence: 78%
“…[16][17][18] Recently, it has been reported that dTAF10 and dTAF10b have synergistic roles in the regulation of Drosophila morphogenesis and they are required for the activation of Halloween genes involved in ecdysone biosynthesis. [18][19][20] Taken together, these observations support the idea that functionally different TAFcontaining complexes participate in gene regulation.…”
Section: Introductionsupporting
confidence: 78%
“…Absorbance was read at 450 nm using a MultiscanPlus II Spectrophotometer (Labsystems, Ramat-Gan, Israel). The ecdysteroid antiserum has the same affinity for ecdysone and 20E, 59 but because the standard curve was obtained with the latter, results are expressed as 20E equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…these two seemingly opposing roles are suggested to maintain the normal balance between the two forms of the hormone during fly development. 71 In conclusion, transcription co-factors such as ssDP, CHIP/LDB and LMo can exert profound effects on the function of the transcription factors they bind. the transcription complexes formed by these interactions are subjected to delicate regulation depending on availability of the co-factors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
“…Indeed, the two Drosophila Hat complexes, dataC and dsaGa, which share both the catalytic unit dGCn5 and the adaptor unit aDa3 but differ in the aDa2a or aDa2b subunits respectively, have very different effects on transcriptional gene regulation. [70][71][72] Interestingly, the dataC complex positively regulates genes that participate in the synthesis of the steroid hormone ecdysone in the prothoracic gland. In contrast, this complex negatively regulates the cells the LDB-Gata complex binds to the promoter of the P4.2 gene.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%